Analisis Sport Tourism Pantai Tirta Samudera di Kabupaten Jepara - Muhamad Asnan Maulana; Tubagus Herlambang; Yulia Ratimiasih (YLPK Mahardhika, 2020)
This research is motivated by the development of the sports sector which is growing rapidly, one of the things that needs to be developed is the type of natural tourism such as on the beach, namely sports tourism activities, including diving, surfing, rolling donuts, namely sitting on a buoy. which looks like a donut, Banana Boat using a banana-shaped rubber boat, and Jet ski. This study uses a qualitative research method in the form of spoken or written words that are observed by researchers, and objects that are observed in detail so that the implied meaning in the document or object can be captured. With the determination of the sample data sources are selected purposively and are snowball sampling, namely the source of information data from the Tourism Office, the Head of the Management of Sport Tourism rides and tourists visiting the Sport Tourism rides. The research location is at Tirta Samudera Beach, the focus of this research is to find out how to analyze the Sport Tourism of Tirta Samudera Beach in Jepara Regency. The data collection techniques and instruments used in this study are using observation, interviews and documentation. The results of this study indicate that the first from the Tourism Office revealed a strategy or effort from the Tourism Office in introducing or promoting the Tirta Samudera Beach Sport Tourism vehicle in Jepara Regency, namely through a website or brochure. The second head of the manager of the Sport Tourism vehicle revealed that in 2020 the rides that have been developing so far are Banana Boat and adding types of Rolling Donuts, Jet Ski, and Kano rides while in the planning stage, namely Flaying Fish and Pareseling which have the same thing being pulled into the air using a Jet Ski. The third is that respondents from tourists enjoying various rides such as Jet Ski, Banana Boat, and Canoe feel their own satisfaction because of their need to exercise. The conclusion is that the Tirta Samudera Beach Sport Tourism rides in Jepara Regency include Banana Boat, Rolling Donuts, Canoe and Jet Ski and from the tourists who enjoy the Sport Tourism rides can feel satisfaction because their need to exercise there are suggestions, namely from the Tourism Office and the Management the Tirta Samudera Beach Sport Tourism vehicle needs to further improve the promotion system or the introduction of Sport Tourism rides through social media or print media so that it can be known by the public who wants to visit. Keywords: Sport Tourism, Tirta Samudera Beach, Sport Abstrak Penelitian ini di latar belakangi oleh perkembangan sektor olahraga yang berkembang pesat, salah satu hal yang perlu dikembangkan yaitu adalah jenis wisata alam seperti di pantai yaitu kegiatan Sport Tourism antara lain menyelam (diving), berselancar (surfing), Rolling Donuts yaitu duduk di sebuah pelampung yang bentuknya seperti kue donat, Banana Boat dengan menggunakan perahu karet berbentuk pisang, dan Jet ski. Penelitian ini menggunakan metode penelitian kualitatif yang berupa kata-kata lisan atau tertulis yang dicermati oleh peneliti, dan benda-benda yang diamati sampai detailnya agar dapat ditangkap makna yang tersirat dalam dokuman atau bendanya. Dengan penetapan sampel sumber data dipilih secara purposive dan bersifat snowball sampling yaitu sumber data informasi dari Dinas Pariwisata, Kepala Pengelola wahana Sport Tourism dan para wisatawan yang mengunjungi wahana Sport Tourism. Lokasi penelitian di Pantai Tirta Samudera, fokus penelitian ini adalah untuk mengetahui bagaimana analisis Sport Tourism Pantai Tirta Samudera di Kabupaten Jepara Adapun teknik dan instrumen pengumpulan data yang digunakan dalam penelitian ini adalah menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukan bahwa yang pertama dari Dinas Pariwisata mengungkapkan adanya strategi atau upaya dari pihak Dinas Pariwisata dalam mengenalkan atau mempromosikan wahana Sport Tourism Pantai Tirta Samudera di Kabupaten Jepara yaitu melalui website atau brosur. Yang kedua dari kepala Pengelola wahana Sport Tourism mengungkapkan pada tahun 2020 wahana yang sampai saat ini berkembang yaitu Banana Boat dan menambahi jenis wahana Rolling Donuts, Jet Ski, dan Kano sedangkan dalam tahap perencanaan yaitu Flaying Fish dan Pareseling yang memiliki persamaan ditarik ke udara menggunakan Jet Ski. Yang ketiga yaitu responden dari wisatawan menikmati berbagai wahana seperti Jet Ski, Banana Boat, dan Kano merasakan kepuasan tersendiri karena kebutuhan mereka untuk berolahraga. Simpulan yaitu wahana Sport Tourism Pantai Tirta Samudera di Kabupaten Jepara antara lain Banana Boat, Rolling Donuts, Kano dan Jet Ski dan dari para wisatawan yang menikmati wahana Sport Tourism dapat merasakan kepuasan karena kebutuhan mereka untuk berolahraga terdapat saran yaitu dari pihak Dinas Pariwisata maupun pihak Pengelola wahana Sport Tourism Pantai Tirta Samudera perlu meningkatkan lagi sistem promosi atau pengenalan wahana Sport Tourism melalui media sosial atau media cetak agar dapat diketahui oleh masyarakat yang ingin berkunjung. Kata Kunci: Sport Tourism, Pantai Tirta Samudera, Sport